Carne y narración. Una reflexión sobre el sí mismo carnal y el yo narrativo en la constitución de la identidad personal - Mercado Vásquez, Martin (2020)
Two approaches can be distinguished in the study of human subjectivity, the phenomenological and the constructivist. The first begins with the description and reflection of the experience of the individual self; the second, instead, focuses on the explanation of the self through the construction of a narrative identity, socially mediated by language. The question that allows us to compare these two theses is this: is the self the illusion of personal identity that occurs as a result of the socially mediated narrative identity or, on the contrary, is the narrative identity the result of a socially extended self? The purpose of this article is, first, to justify the chosen problem in context (1). He then tackles the constructivist thesis based on the contributions of Daniel Dennet and Pierre Bourdieu, considering its practical repercussions (2). The phenomenological position is then presented, considering three different contributions, that of Dan Zahavi, Hermann Schmitz and Thomas Fuchs. Finally, by way of conclusion, it is affirmed that personal identity implies the subjective experience of a carnal self that is the foundation of the narrative self.